Emergent decision-making practices in technology-supported self-organizing distributed teams - Heckman, Robert; Kevin Crowston; Li, Qing; Allen, Eileen E.; Eseryel, U. Yeliz; James Howison; Kangning Wei (Proceedings of the International Conference on Information Systems (ICIS), 2006)
We seek to identify work practices that make technology-supported self-organizing distributed (or virtual) teams (TSSODT for short) effective in producing outputs satisfactory to their sponsors, meeting the needs of their members and continuing to function. A particularly important practice for team effectiveness is decision making: are the right decisions made at the right time to get the work done in a way that satisfies team sponsors, keeps contributors happy and engaged, and enables continued team success? In this research-in-progress paper, we report on an inductive qualitative analysis of 120 decision episodes taken by 2 Free/libre Open Source Software development teams. Our analysis revealed differences in decision-making practices that seem to be related to differences in overall team effectiveness.
Keywords: Decision-Making; FLOSS